2019
DOI: 10.1093/ije/dyz200
|View full text |Cite
|
Sign up to set email alerts
|

Education protects against coronary heart disease and stroke independently of cognitive function: evidence from Mendelian randomization

Abstract: Background There is evidence that education protects against cardiovascular disease. However, it is not known whether such an effect is independent of cognition. Methods We performed two-sample Mendelian randomization (MR) analyses to investigate the effect of education and cognition, respectively, on risk of CHD and ischaemic stroke. Additionally, we used multivariable MR to adjust for the effects of cognition and education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 59 publications
2
79
0
Order By: Relevance
“…In fact, the findings from another recent two-sample MR study, which investigated the impact of education and cognitive ability in a multivariable model in relation to CHD, provide evidence that intelligence is unlikely to be the important driver, at least in relation to CHD. Gill et al found that more schooling years, independent of cognitive ability, are protective: OR 0.76; 95% CI 0.65-0.89 26 .…”
Section: Triglyceride Levelsmentioning
confidence: 99%
“…In fact, the findings from another recent two-sample MR study, which investigated the impact of education and cognitive ability in a multivariable model in relation to CHD, provide evidence that intelligence is unlikely to be the important driver, at least in relation to CHD. Gill et al found that more schooling years, independent of cognitive ability, are protective: OR 0.76; 95% CI 0.65-0.89 26 .…”
Section: Triglyceride Levelsmentioning
confidence: 99%
“…These two-sample MR analyses were conducted based on de-identified summary-concentrations data that have been made publicly available; ethical approval was obtained in all original studies. MR analyses assessed the casual effect of an exposure on an outcome by using SNPs as instrumental variables (IVs), in the presence of unmeasured confounding, given that the genotypes are conditionally independent of the disease status [17][18][19]. The following assumptions are made for MR inference: first, the genetic variant has a robust causal relationship with the exposure; second, the genetic variant affects the outcome only through its effect on the exposure; third, the genetic variant and the outcome do not have common causes (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These two-sample MR analyses were conducted based on de-identi ed summary-concentrations data that have been made publicly available; ethical approval was obtained in all original studies. MR analyses assessed the casual effect of an exposure on an outcome by using SNPs as instrumental variables (IVs), in the presence of unmeasured confounding, given that the genotypes are conditionally independent of the disease status [17][18][19]. The following assumptions are made for MR inference: rst, the genetic variant has a robust causal relationship with the exposure; second, the genetic variant affects the outcome only through its effect on the exposure; third, the genetic variant and the outcome do not have common causes (Fig.…”
Section: Methodsmentioning
confidence: 99%